Domination number on an octagonal chain and an octagonal grid - Mihajlov Carević, Miroslava (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 519.1Domination of the graph and topological indices are essential topics in the graph theory. We analyze the problem of $k$-domination, $k\in\{1,2,3\}$, on octagonal chains and an octagonal grid. We determine the minimal $k$-dominating sets and  $k$-domination $k$ numbers for a chain of octagons with two common vertices. By using the obtained results, we determine the $k$-domination numbers for the grid of octagons  $O_{mxn}$ with $m,n\in N$.